Increasing Winter Ocean‐to‐Ice Heat Flux in the Beaufort Gyre Region, Arctic Ocean Over 2006–2018. Issue 2 (21st January 2022) - Zhong, Wenli; Cole, Sylvia T.; Zhang, Jinlun; Lei, Ruibo; Steele, Michael
Abstract: Ocean‐to‐ice heat flux (OHF) is important in regulating the variability of sea ice mass balance. Using surface drifting buoy observations, we show that during winter in the Arctic Ocean's Beaufort Gyre region, OHF increased from 0.76 ± 0.05 W/m 2 over 2006–2012 to 1.63 ± 0.08 W/m 2 over 2013–2018. We find that this is a result of thinner and less‐compact sea ice that promotes enhanced winter ice growth, stronger ocean vertical convection, and subsurface heat entrainment. In contrast, Ekman upwelling declined over the study period, suggesting it had a secondary contribution to OHF changes. The enhanced ice growth creates a cooler, saltier, and deeper ocean surface mixed layer. In addition, the enhanced vertical temperature gradient near the mixed layer base in later years favors stronger entrainment of subsurface heat. OHF and its increase during 2006–2018 were not geographically uniform, with hot spots found in an upwelling region where ice was most seasonally variable. Plain Language Summary: Heat transferred from the ocean to the sea ice influences the extent to which sea ice melts or freezes. It is unclear how variable this heat transfer is during winter. Using multiple drifting instruments, our results reveal that ocean‐to‐ice heat transfer almost doubled from 2006–2012 to 2013–2018. The enhanced heat transfer is a result of thinner and looser sea ice that leads to enhanced ice growth during winter. This enhanced ice growth causes stronger mixing within the ocean and so larger transfers of heat from the ocean to the ice. Changes in the extent to which water is physically pushed upwards had a secondary role in enhanced ocean‐to‐ice heat transfer over the study period. As a result of the increased ice growth, the pool of water directly in contact with the ice cover is cooler, saltier, and deeper over 2013–2018 compared with 2006–2012. Changes in ocean temperature at depth additionally favor stronger subsurface heat entrainment during 2013–2018. Ocean‐to‐ice heat transfer and its increase during 2006–2018 was not geographically uniform, with hot spots found where ice was most seasonally variable. Key Points: The winter ocean‐to‐ice heat flux increased by 0.87 ± 0.09 W/m 2 from 2006–2012 to 2013–2018 in the Beaufort Gyre region 2013–2018, compared with 2006–2012, had stronger convection associated with thinner ice, and increased ice mobility and lead fraction Changes to Ekman upwelling had a secondary role in enhanced heat flux and entrainment of subsurface heat